Temperature-dependent magnetic and electrical properties of Cr-doped AlFeO3 ceramics. Issue 4 (1st October 2020) - Raies, Imen; Al Dulmani, Sharah A.; Ben Farhat, Lamia; Fadlallah, Etemad E.; Amami, Mongi
ABSTRACT: The solid-state reaction method was selected to prepare polycrystalline AlFe1− x Cr x O3 ( x = 0, 0.02, 0.05, 0.07 and 0.1) samples. The Samples were found to be pure phases possessing the orthorhombic space group Pna 21. The unit cell volume decreased with increases in the Cr content. The magnetic transition temperature and the saturation magnetization of the ceramics decreased due to dilution of the magnetic interaction with Cr content. The Dielectric responses were systematically investigated by temperature-dependent dielectric/impedance spectroscopy from 160 K to 500 K. It was noticed that incorporation of Cr 3+ in the structure led to an increase in the dielectric constant up to x = 0.05 before decreasing, whereas the dielectric loss decreased. Two different dielectric relaxation processes that occurred in the grain interior of AlFe1-x Crx O3 polycrystals were clarified. One relaxation process was thought to be associated with localized transfer of electrons between Fe 3+ and Fe 2+, while the other arising at low temperature was assigned to interplay between lattice and polaronic defects such as oxygen vacancies.